2014
DOI: 10.1111/jipb.12212
|View full text |Cite
|
Sign up to set email alerts
|

Rice CYP703A3, a cytochrome P450 hydroxylase, is essential for development of anther cuticle and pollen exine

Abstract: Anther cuticle and pollen exine act as protective envelopes for the male gametophyte or pollen grain, but the mechanism underlying the synthesis of these lipidic polymers remains unclear. Previously, a tapetum-expressed CYP703A3, a putative cytochrome P450 fatty acid hydroxylase, was shown to be essential for male fertility in rice (Oryza sativa L.). However, the biochemical and biological roles of CYP703A3 has not been characterized. Here, we observed that cyp703a3-2 caused by one base insertion in CYP703A3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
176
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(181 citation statements)
references
References 62 publications
(163 reference statements)
5
176
0
Order By: Relevance
“…Previous reports showed that plastids could not been found in anther epidermal cells (Mamun et al, 2005a(Mamun et al, , 2005b, which implies that lipid de novo synthesis cannot occur within anther epidermal cells. Therefore, it is not surprising that several tapetum-expressed lipid metabolism genes are involved in anther cuticle formation (Li et al, 2010;Shi et al, 2011;Yang et al, 2014). Here, we observed that OsABCG26 is localized to the plasma membrane of anther wall layers at stage 9 during anther development, and mutation of OsABCG26 leads to detective anther cuticle and pollen exine, suggesting that cuticular lipids are produced in the tapetum, from which they are exported or distributed by OsABCG26.…”
Section: Anther Cuticle and Pollen Exine Share One Common Aliphatic Smentioning
confidence: 58%
See 4 more Smart Citations
“…Previous reports showed that plastids could not been found in anther epidermal cells (Mamun et al, 2005a(Mamun et al, , 2005b, which implies that lipid de novo synthesis cannot occur within anther epidermal cells. Therefore, it is not surprising that several tapetum-expressed lipid metabolism genes are involved in anther cuticle formation (Li et al, 2010;Shi et al, 2011;Yang et al, 2014). Here, we observed that OsABCG26 is localized to the plasma membrane of anther wall layers at stage 9 during anther development, and mutation of OsABCG26 leads to detective anther cuticle and pollen exine, suggesting that cuticular lipids are produced in the tapetum, from which they are exported or distributed by OsABCG26.…”
Section: Anther Cuticle and Pollen Exine Share One Common Aliphatic Smentioning
confidence: 58%
“…It is generally accepted that sporopollenin, the pollen exine constituent, is produced exclusively in tapetum, and many genes involved in lipid synthesis and exine formation were identified in tapetum (Li et al, 2010;Quilichini et al, 2010Quilichini et al, , 2014Ariizumi and Toriyama, 2011;Chen et al, 2011b;Shi et al, 2011;Zhu et al, 2013;Lou et al, 2014;Yang et al, 2014). However, there is no Figure 11.…”
Section: Anther Cuticle and Pollen Exine Share One Common Aliphatic Smentioning
confidence: 97%
See 3 more Smart Citations